A coating material for anode copper casting and preparation method thereof

By using coating materials composed of magnesium chromium oxide, aluminum silicon powder, flame-retardant modified bentonite, modified carboxymethyl cellulose and silane coupling agent ETP, the poor bonding strength and erosion resistance of existing coating materials are solved. To solve the problem of insufficient performance, a coating material with high adhesion and flame retardant properties is realized to extend the service life of the mold.

CN118637894BActive Publication Date: 2025-01-21LUOYANG BOXIN REFRACTORY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411114508.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-01-21
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing anode copper casting coatings have poor bonding strength, uneven coating, insufficient anti-shrink and corrosion resistance, which cannot meet the normal use needs of the anode plate.

Method used

Using components such as magnesium chromium oxide, aluminum silicon powder, flame-retardant modified bentonite, modified carboxymethyl cellulose and silane coupling agent ETP, the adhesiveness and suspension of the coating material are improved through the preparation method of modified bentonite. performance, enhancing the bonding strength with the copper mold anode plate.

Benefits of technology

It significantly improves the adhesion, suspension and flame retardant properties of the coating material, enhances the bonding strength with the copper mold anode plate, and extends the service life of the mold.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of refractory materials, and specifically relates to a coating material for anode copper casting and a preparation method thereof. The coating material includes the following components in parts by weight: 60-70 parts of magnesium chromium oxide, 25-35 parts of aluminum silicon powder, 1-3 parts of flame retardant modified bentonite, 0.1-0.3 parts of modified carboxymethyl cellulose, 3-6 parts of silane coupling agent ETP, and 0.05-0.1 parts of explosion-proof fiber; the preparation method of the flame retardant modified bentonite is: firstly modifying o-cresol epoxy resin with triphenyl phosphate to prepare flame retardant epoxy resin, then modifying silica sol with flame retardant epoxy resin to prepare organic modified silica sol, and finally modifying bentonite with organic modified silica sol to prepare flame retardant modified bentonite. The coating material prepared by the present invention has good flame retardancy, suspension and leveling properties, high bonding strength, good spreadability, can effectively reduce mold cracking, and improve the service life of the mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a coating material for anode copper casting and a preparation method thereof. Background Art

[0002] In the copper smelting industry, magnesia-chrome refractory bricks are selected as the working layer of refractory materials for furnace masonry in consideration of the characteristics of the smelting process. However, the waste magnesia-chrome bricks replaced during maintenance will infiltrate a large amount of valuable metals such as copper, and the copper content of the crushed powder of waste magnesia-chrome bricks in the anode furnace is as high as 5%. Therefore, waste magnesia-chrome bricks can be used as test materials to develop a coating for anode copper casting to solve the problem of resource utilization of waste magnesia-chrome bricks in copper smelting. However, the bonding strength between the copper mold and the coating is poor, the coating is uneven, and the anti-scouring and anti-erosion performance is poor, which cannot meet the normal use of the anode plate.

[0003] The patent with application number 202211066837.7 provides a resource utilization method for waste magnesia-chrome bricks from copper smelting, including the following weight proportions: the powder of waste magnesia-chrome bricks from copper smelting after crushing and grinding is 45wt% according to the particle size <1mm, 25wt% according to the particle size 1-3mm, and 30wt% according to the particle size 3-5mm; 20-30% of waste magnesia-chrome brick powder of different particle sizes, 60-70% of aluminum silicon powder, 10% of calcium aluminate cement, and 0.05% of explosion-proof fiber, and the sum of their weight percentages is 100%. The coating material for anode copper casting provided by the invention avoids the loss of valuable metals such as copper and the impact of concentrated treatment of a large amount of waste magnesia-chrome brick powder containing MgO and Cr2O3 on the smelting furnace conditions, and also reduces the purchase cost of the coating material for anode copper casting, but the use of cement as a binder has defects such as large water consumption, complex later maintenance, and high medium-temperature strength of the castable. The patent with application number 201710367967.7 provides a copper anode casting mold repair material and its application, including the following weight components: 20-30% magnesium chromium oxide, 20-60% aluminum oxide, 20-60% silicon carbide, magnesium chromium oxide, aluminum oxide, silicon carbide constitute 100% solid material by mass, and the liquid-solid ratio of aluminum phosphate adhesive to solid material is 0.6-0.9:1. The copper anode casting mold repair material coating provided by the invention is bonded to the mold, and the crack repair coating has a certain strength after curing to fill the cracks, but the aluminum phosphate adhesive has the adverse effect of promoting the powdering of refractory fibers and is prone to cracks and other defects when baked at high temperatures. Summary of the invention

[0004] The purpose of the present invention is to provide a coating material for anode copper casting and a preparation method thereof in view of the deficiencies in the prior art. The coating material prepared by the present invention has good adhesion, is easy to demould, reduces mold cracking, and increases the service life of the mold.

[0005] The technical solution of the present invention to solve the above problems is as follows:

[0006] A coating material for anode copper casting, comprising the following components in parts by weight: 60-70 parts of magnesium chromium oxide, 25-35 parts of aluminum silicon powder, 1-3 parts of flame retardant modified bentonite, 0.1-0.3 parts of modified carboxymethyl cellulose (modified CMC), 3-6 parts of silane coupling agent ETP, and 0.05-0.1 parts of explosion-proof fiber;

[0007] The preparation method of the flame retardant modified bentonite is:

[0008] Step S1, adding o-cresol epoxy resin, triphenyl phosphate and dicyandiamide to a mixed solution of N-methylformamide and acetone in sequence, stirring and mixing evenly, heating and refluxing at 150-170° C. for reaction for 3-6 hours, removing the solvent, and obtaining a flame retardant epoxy resin; the mass ratio of the o-cresol epoxy resin, triphenyl phosphate, dicyandiamide, N-methylformamide and acetone is 20:6-10:0.5-1.5:4-6:4-6;

[0009] Step S2, in a protective atmosphere and under stirring conditions, ethyl acetate and acetone are uniformly mixed to obtain a mixed solvent, the flame retardant epoxy resin obtained in step S1 is dissolved in the mixed solvent, and then silica sol is added, and the mixture is reacted at a constant temperature of 55-75° C. for 1-4 hours, the solvent is removed, and the mixture is dried to obtain modified silicon dioxide particles, and the modified silicon dioxide particles are redispersed in deionized water to obtain an organic modified silica sol; the mass ratio of the flame retardant epoxy resin to the silica sol is 0.5-1.5:20, and the amount of the flame retardant epoxy resin added to the mixed solvent is 0.05-0.2 g / mL; the mass percentage of silicon dioxide in the silica sol is 30-40%, and the particle size is 50-100 nm;

[0010] Step S3, at room temperature, adding the organic modified silica sol obtained in step S2 and the pretreated sodium bentonite to deionized water, stirring evenly, aging for 6-12 hours, filtering, drying, and crushing to obtain flame retardant modified bentonite. The mass ratio of the organic modified silica sol to the pretreated sodium bentonite is 0.5-2:8; the pretreatment process of the sodium bentonite is: after roasting at 400-500°C, crushing and sieving to obtain pretreated bentonite with a particle size of 150-200 mesh.

[0011] Furthermore, the particle size distribution of the magnesium chromium oxide is: <1 mm accounts for 45%, 1-3 mm accounts for 25%, 3-5 mm accounts for 30%, and the main components (by mass percentage) are: Mg: 23.67-25.42%, Cr: 2.42-3.11%, Cu: 6.52-6.88%, Fe: 3.87-4.22%.

[0012] Furthermore, the particle size distribution of the aluminum silicon powder is: <1mm accounts for 15%, 1-3mm accounts for 25%, 3-6mm accounts for 35%, and >6mm accounts for 25%. The main components (by mass percentage) are: SiO2: 25%, Al2O3: 60%, CaO: 1.75%.

[0013] Furthermore, the preparation method of the modified CMC is as follows: at room temperature and under stirring conditions, carboxymethyl cellulose is completely dissolved in deionized water, octylphenol polyoxyethylene ether and dibutyltin dilaurate are added respectively, mixed evenly, and then diphenylmethane diisocyanate is added to carry out a cross-linking reaction, the cross-linking temperature is 25-35°C, the cross-linking time is 30-60min, and vacuum drying is performed to obtain modified carboxymethyl cellulose; the mass ratio of the CMC, octylphenol polyoxyethylene ether, dibutyltin dilaurate, and MDI is 60:1-2:2-4:20-30; and the mass percentage of CMC in the deionized water is 2-4%.

[0014] Furthermore, the preparation method of the silane coupling agent ETP is as follows: under normal temperature and pressure conditions, 3-isocyanate propyl triethoxysilane and m-aminophenylacetylene are added to tetrahydrofuran (THF), the reaction is stirred for 1-3 hours, THF is evaporated to obtain a light yellow viscous liquid, and the liquid is allowed to stand at room temperature until yellow-white spherulites are precipitated, which is the silane coupling agent ETP; the amount of 3-isocyanate propyl triethoxysilane added to the tetrahydrofuran is 0.15-0.2 g / mL, and the amount of m-aminophenylacetylene added to the tetrahydrofuran is 0.06-0.1 g / mL.

[0015] The present invention also provides a method for preparing a coating material for anode copper casting, comprising the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, silane coupling agent ETP, and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0016] The present invention has the following beneficial effects:

[0017] The present invention firstly modifies o-cresol epoxy resin with triphenyl phosphate to prepare flame retardant epoxy resin. The triphenyl phosphate in the flame retardant epoxy resin is decomposed into phosphoric acid and metaphosphoric acid under high temperature, and finally generates polymetaphosphoric acid. The polymetaphosphoric acid is a stable compound that is not easy to volatilize, which prompts the surface of the epoxy resin to be rapidly dehydrated and carbonized, thereby forming a protective layer on the surface of the coating material to play a flame retardant role. The present invention further modifies silica sol with flame retardant epoxy resin, introduces organic high molecular polymer on the surface of the modified silica sol, improves its compatibility with raw material components such as modified carboxymethyl cellulose, and further improves the interaction force between the raw material components, thereby improving the density of the coating material. The present invention finally uses organic modified silica sol The bentonite containing montmorillonite is modified by the organic modified silica sol with multivalent negative charge, which easily reacts with the aluminum ions exposed on the end faces of montmorillonite and adsorbs on their end faces, thereby making the bentonite particles carry negative charge. Like charges repel each other, and the particles are difficult to aggregate into large particles, so the suspension performance is greatly improved. In addition, the organic modified silica sol also has excellent bonding effect, so that when bentonite is used as a system suspending agent, it can not only improve the suspension of the system, but also further improve the density of the coating, thereby improving the mechanical strength of the coating; and the organic modified silica sol is grafted onto the surface of the bentonite particles, which can further improve the compatibility of the flame retardant modified bentonite and modified carboxymethyl cellulose.

[0018] The present invention utilizes the hydroxyl group in the carboxymethyl cellulose structure to react with the isocyanate group of diphenylmethane diisocyanate to generate an amide group to prepare a modified carboxymethyl cellulose, which has excellent suspension and adhesion properties and synergistically acts with flame-retardant modified bentonite to significantly improve the dispersion of the coating and greatly enhance the bonding strength between the coating and the copper mold anode plate.

[0019] The silane coupling agent ETP prepared by the present invention can be used as an adhesive, and the molecular structure of the silane coupling agent ETP contains both silane ethoxy and alkynyl groups. The multifunctional silane coupling agent can enhance the chemical bonding and hydrogen bonding between the components of the coating, thereby improving the interface bonding performance of the composite material. By compounding the flame-retardant modified bentonite, modified carboxymethyl cellulose, and the silane coupling agent ETP, the bonding strength between the components of the coating and the coating and the copper mold anode plate is significantly enhanced, and the protective function of the coating can be fully exerted. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0021] Magnesium chromium oxide, prepared by crushing waste magnesium chromium bricks, with particle sizes of <1mm, 1-3mm, 3-5mm, and main components (by mass percentage): Mg: 23.67-25.42%, Cr: 2.42-3.11%, Cu: 6.52-6.88%, Fe: 3.87-4.22%; aluminum silicon powder, with particle sizes of <1mm, 1-3mm, 3-6mm, >6mm, and main components (by mass percentage): SiO2: 25%, Al2O3: 60%, CaO: 1.75%; o-cresol cyclopentane Epoxy resin, epoxy value is 0.45-0.50mol / 100g, molecular weight is 20000; silica sol, silica mass percentage is 30-40%, particle size is 50-100nm; sodium bentonite, montmorillonite mass percentage is ≥60%, particle size is 100-200 mesh; carboxymethyl cellulose, viscosity is 50-100mpa·s, molecular weight is 90000, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; explosion-proof fiber, fire resistant temperature is 165℃, compressive strength is ≥560MPa, purchased from Wuhan Qixing New Technology Research Institute. The raw materials used in the following examples are all common commercially available products.

[0022] Example 1

[0023] A coating material for anode copper casting comprises the following components in parts by weight: 60 parts of magnesium chromium oxide, 25 parts of aluminum silicon powder, 1 part of flame retardant modified bentonite, 0.1 part of modified CMC, 3 parts of silane coupling agent ETP, and 0.1 part of explosion-proof fiber.

[0024] Among them, magnesium chromium oxide is prepared by crushing waste magnesium chromium bricks, and the particle size distribution is: <1mm accounts for 45%, 1-3mm accounts for 25%, 3-5mm accounts for 30%, and the main components (by mass percentage) are: Mg: 23.67%, Cr: 2.42%, Cu: 6.52%, Fe: 3.87%; the mass percentage of silicon dioxide in the silica sol is 30%, and the particle size is 50-100nm; the particle size distribution of aluminum silicon powder is: <1mm accounts for 15%, 1-3mm accounts for 25%, 3-6mm accounts for 35%, and >6mm accounts for 25%.

[0025] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0026] Wherein, the preparation method of flame retardant modified bentonite is:

[0027] Step S1, to a mixed solution of 4g N-methylformamide and 4g acetone, 20g o-cresol epoxy resin, 6g triphenyl phosphate, and 0.500g dicyandiamide were added in sequence, the mixture was stirred and mixed evenly, and the mixture was heated under reflux at 160°C for 4h, and the solvent was removed to obtain a flame retardant epoxy resin;

[0028] Step S2, in a nitrogen atmosphere and under stirring conditions, 100 mL of ethyl acetate and 100 mL of acetone are mixed uniformly to obtain a mixed solvent, 10 g of the flame-retardant epoxy resin obtained in step S1 is dissolved in the mixed solvent, and 400 g of silica sol is added, and the mixture is reacted at a constant temperature of 60° C. for 2 h, the solvent is removed, and the mixture is dried to obtain modified silica particles, and the modified silica particles are redispersed in deionized water to obtain an organic modified silica sol; the mass percentage of silica in the organic modified silica sol is 40%, and the particle size is 80-150 nm;

[0029] Step S3, at room temperature, add 10g of the organic modified silica sol obtained in step S2 and 40g of sodium bentonite with a particle size of 150-200 mesh obtained by calcining, crushing and sieving at 450°C to 200mL of deionized water, stir evenly, age for 8h, filter, vacuum dry to constant weight, and crush to obtain flame retardant modified bentonite; the particle size of the flame retardant modified bentonite is 150-300 mesh.

[0030] The preparation method of modified CMC is as follows: CMC is completely dissolved in deionized water at a stirring rate of 300 r / min under room temperature, the mass percentage of CMC is 3%, 0.100g of non-ionic surfactant octylphenol polyoxyethylene ether and 0.150g of catalyst dibutyltin dilaurate are added respectively, mixed evenly, and then 1.250g of MDI is added for cross-linking reaction, the cross-linking temperature is 30°C, the cross-linking time is 45min, and vacuum drying is carried out at 60°C for 12h to obtain modified carboxymethyl cellulose; the mass ratio of the CMC, octylphenol polyoxyethylene ether, dibutyltin dilaurate and MDI is 60:2:3:25.

[0031] The preparation method of the silane coupling agent ETP is as follows: under normal temperature and pressure conditions, 18 g of 3-isocyanatepropyltriethoxysilane and 8 g of m-aminophenylacetylene are added to 100 mL of THF, and the mixture is stirred for reaction for 2 h. THF is evaporated to obtain a light yellow viscous liquid, which is allowed to stand at room temperature until yellow-white spherulites are precipitated, which is the silane coupling agent ETP.

[0032] Example 2

[0033] A coating material for anode copper casting comprises the following components in parts by weight: 65 parts of magnesium chromium oxide, 35 parts of aluminum silicon powder, 3 parts of flame retardant modified bentonite, 0.3 parts of modified CMC, 6 parts of silane coupling agent ETP, and 0.05 parts of explosion-proof fiber.

[0034] Among them, magnesium chromium oxide is prepared by crushing waste magnesium chromium bricks, and the particle size distribution is: <1mm accounts for 45%, 1-3mm accounts for 25%, 3-5mm accounts for 30%, and the main components (by mass percentage) are: Mg: 25.42%, Cr: 3.11%, Cu: 6.88%, Fe: 4.22%; the mass percentage of silicon dioxide in the silica sol is 40%, and the particle size is 50-100nm; the particle size distribution of aluminum silicon powder is: <1mm accounts for 15%, 1-3mm accounts for 25%, 3-6mm accounts for 35%, and >6mm accounts for 25%.

[0035] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0036] Wherein, the preparation method of flame retardant modified bentonite is:

[0037] Step S1, to a mixed solution of 6g N-methylformamide and 6g acetone, 20g o-cresol epoxy resin, 10g triphenyl phosphate, and 1.500g dicyandiamide were added in sequence, the mixture was stirred and mixed evenly, and the mixture was heated under reflux at 170°C for 6h, and the solvent was removed to obtain a flame retardant epoxy resin;

[0038] Step S2, in a nitrogen atmosphere and under stirring conditions, 100 mL of ethyl acetate and 100 mL of acetone were mixed uniformly to obtain a mixed solvent, 30 g of the flame-retardant epoxy resin obtained in step S1 was dissolved in the mixed solvent, and 400 g of silica sol was added, and the mixture was reacted at a constant temperature of 75° C. for 4 h, the solvent was removed, and the mixture was dried to obtain modified silica particles, and the modified silica particles were redispersed in deionized water to obtain an organic modified silica sol; the mass percentage of silica in the organic modified silica sol was 35%, and the particle size was 80-150 nm;

[0039] Step S3, at room temperature, add 10g of the organic modified silica sol obtained in step S2 and 40g of sodium bentonite with a particle size of 150-200 mesh obtained by calcining, crushing and sieving at 500°C to 200mL of deionized water, stir evenly, age for 12h, filter, vacuum dry to constant weight, and crush to obtain flame retardant modified bentonite; the particle size of the flame retardant modified bentonite is 150-300 mesh.

[0040] The preparation method of modified CMC is as follows: CMC is completely dissolved in deionized water at a stirring rate of 300 r / min under room temperature, the mass percentage of CMC is 4%, 0.133g of non-ionic surfactant octylphenol polyoxyethylene ether and 0.267g of catalyst dibutyltin dilaurate are added respectively, mixed evenly, and then 2g of MDI is added for cross-linking reaction, the cross-linking temperature is 35°C, the cross-linking time is 60min, and vacuum drying is carried out at 60°C for 12h to obtain modified carboxymethyl cellulose; the mass ratio of the CMC, octylphenol polyoxyethylene ether, dibutyltin dilaurate and MDI is 60:2:4:30.

[0041] The preparation method of the silane coupling agent ETP is as follows: under normal temperature and pressure conditions, 20 g of 3-isocyanatepropyltriethoxysilane and 10 g of m-aminophenylacetylene are added to 100 mL of THF, and the mixture is stirred for reaction for 3 h. THF is evaporated to obtain a light yellow viscous liquid, which is allowed to stand at room temperature until yellow-white spherulites are precipitated, which is the silane coupling agent ETP.

[0042] Example 3

[0043] A coating material for anode copper casting comprises the following components in parts by weight: 70 parts of magnesium chromium oxide, 30 parts of aluminum silicon powder, 2 parts of flame retardant modified bentonite, 0.2 parts of modified CMC, 5 parts of silane coupling agent ETP, and 0.08 parts of explosion-proof fiber.

[0044] Among them, magnesium chromium oxide is prepared by crushing waste magnesium chromium bricks, and its particle size distribution is: <1mm accounts for 45%, 1-3mm accounts for 25%, 3-5mm accounts for 30%, and the main components (by mass percentage) are: Mg: 25.42%, Cr: 3.11%, Cu: 6.88%, Fe: 4.22%; the mass percentage of silicon dioxide in the silica sol is 40%, and the particle size is 50-100nm; the particle size distribution of aluminum silicon powder is: <1mm accounts for 15%, 1-3mm accounts for 25%, 3-6mm accounts for 35%, and >6mm accounts for 25%.

[0045] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0046] Wherein, the preparation method of flame retardant modified bentonite is:

[0047] Step S1, to a mixed solution of 5g N-methylformamide and 5g acetone, 20g o-cresol epoxy resin, 8g triphenyl phosphate and 1g dicyandiamide were added in sequence, the mixture was stirred and mixed evenly, and the mixture was heated under reflux at 160°C for 3h, and the solvent was removed to obtain a flame retardant epoxy resin;

[0048] Step S2, in a nitrogen atmosphere and under stirring conditions, 100 mL of ethyl acetate and 100 mL of acetone are mixed uniformly to obtain a mixed solvent, 20 g of the flame-retardant epoxy resin obtained in step S1 is dissolved in the mixed solvent, and 400 g of silica sol is added, and the mixture is reacted at a constant temperature of 55° C. for 1 hour, the solvent is removed, and the mixture is dried to obtain modified silica particles, and the modified silica particles are redispersed in deionized water to obtain an organic modified silica sol; the mass percentage of silica in the organic modified silica sol is 40%, and the particle size is 80-150 nm;

[0049] Step S3, at room temperature, add 5g of the organic modified silica sol obtained in step S2 and 40g of sodium bentonite with a particle size of 150-200 mesh obtained by calcining, crushing and sieving at 450°C to 200mL of deionized water, stir evenly, age for 10h, filter, vacuum dry to constant weight, and crush to obtain flame retardant modified bentonite; the particle size of the flame retardant modified bentonite is 150-300 mesh.

[0050] The preparation method of modified CMC is as follows: CMC is completely dissolved in deionized water at a stirring rate of 300 r / min under room temperature, the mass percentage of CMC is 3.5%, 0.058g of non-ionic surfactant octylphenol polyoxyethylene ether and 0.117g of catalyst dibutyltin dilaurate are added respectively, mixed evenly, and then 1.167g of MDI is added for cross-linking reaction, the cross-linking temperature is 25°C, the cross-linking time is 30min, and vacuum drying is carried out at 60°C for 12h to obtain modified carboxymethyl cellulose; the mass ratio of the CMC, octylphenol polyoxyethylene ether, dibutyltin dilaurate and MDI is 60:1:2:20.

[0051] The preparation method of the silane coupling agent ETP is as follows: under normal temperature and pressure conditions, 15 g of 3-isocyanatepropyltriethoxysilane and 6 g of m-aminophenylacetylene are added to 100 mL of THF, the mixture is stirred for reaction for 1 hour, THF is evaporated to obtain a light yellow viscous liquid, and the liquid is allowed to stand at room temperature until yellow-white spherulites are precipitated, which is the silane coupling agent ETP.

[0052] Example 4

[0053] A coating material for anode copper casting comprises the following components in parts by weight: 60 parts of magnesium chromium oxide, 25 parts of aluminum silicon powder, 1 part of flame retardant modified bentonite, 0.1 part of modified CMC, 3 parts of silane coupling agent ETP, and 0.1 part of explosion-proof fiber.

[0054] Among them, magnesium chromium oxide is prepared by crushing waste magnesium chromium bricks, and the particle size distribution is: <1mm accounts for 45%, 1-3mm accounts for 25%, 3-5mm accounts for 30%, and the main components (by mass percentage) are: Mg: 23.67%, Cr: 2.42%, Cu: 6.52%, Fe: 3.87%; the mass percentage of silicon dioxide in the silica sol is 30%, and the particle size is 50-100nm; the particle size distribution of aluminum silicon powder is: <1mm accounts for 15%, 1-3mm accounts for 25%, 3-6mm accounts for 35%, and >6mm accounts for 25%.

[0055] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0056] Wherein, the preparation method of flame retardant modified bentonite is:

[0057] Step S1, to a mixed solution of 4g N-methylformamide and 4g acetone, 20g o-cresol epoxy resin, 10g triphenyl phosphate, and 0.500g dicyandiamide were added in sequence, the mixture was stirred and mixed evenly, and the mixture was heated under reflux at 150°C for 4h, and the solvent was removed to obtain a flame retardant epoxy resin;

[0058] Step S2, in a nitrogen atmosphere and under stirring conditions, 100 mL of ethyl acetate and 100 mL of acetone were mixed uniformly to obtain a mixed solvent, 40 g of the flame-retardant epoxy resin obtained in step S1 was dissolved in the mixed solvent, and 1200 g of silica sol was added, and the mixture was reacted at a constant temperature of 55° C. for 4 h, the solvent was removed, and the mixture was dried to obtain modified silica particles, and the modified silica particles were redispersed in deionized water to obtain an organic modified silica sol; the mass percentage of silica in the organic modified silica sol was 30%, and the particle size was 80-150 nm;

[0059] Step S3, at room temperature, add 2.500g of the organic modified silica sol obtained in step S2 and 40g of sodium bentonite with a particle size of 150-200 mesh obtained by calcining, crushing and sieving at 450°C to 200mL of deionized water, stir evenly, age for 8h, filter, vacuum dry to constant weight, and crush to obtain flame retardant modified bentonite; the particle size of the flame retardant modified bentonite is 150-300 mesh.

[0060] The preparation method of modified CMC is as follows: CMC is completely dissolved in deionized water at a stirring rate of 300 r / min under room temperature, the mass percentage of CMC is 3%, 0.075g of non-ionic surfactant octylphenol polyoxyethylene ether and 0.150g of catalyst dibutyltin dilaurate are added respectively, mixed evenly, and then 1.500g of MDI is added for cross-linking reaction, the cross-linking temperature is 30°C, the cross-linking time is 45min, and vacuum drying is performed at 60°C for 12h to obtain modified carboxymethyl cellulose; the mass ratio of the CMC, octylphenol polyoxyethylene ether, dibutyltin dilaurate and MDI is 60:1.5:3:30.

[0061] The preparation method of the silane coupling agent ETP is as follows: under normal temperature and pressure conditions, 18 g of 3-isocyanatepropyltriethoxysilane and 8 g of m-aminophenylacetylene are added to 100 mL of THF, and the mixture is stirred for reaction for 2 h. THF is evaporated to obtain a light yellow viscous liquid, which is allowed to stand at room temperature until yellow-white spherulites are precipitated, which is the silane coupling agent ETP.

[0062] Comparative Example 1

[0063] A coating material for anode copper casting, comprising the following components in parts by weight: 70 parts of magnesium chromium oxide, 35 parts of aluminum silicon powder, 3 parts of bentonite, 0.3 parts of modified CMC, 6 parts of silane coupling agent ETP, and 0.1 parts of explosion-proof fiber;

[0064] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, bentonite, modified carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0065] The preparation method of modified CMC and silane coupling agent ETP is the same as that in Example 1.

[0066] Comparative Example 2

[0067] A coating material for anode copper casting, comprising the following components in parts by weight: 70 parts of magnesium chromium oxide, 35 parts of aluminum silicon powder, 3 parts of flame retardant modified bentonite, 0.3 parts of CMC, 6 parts of silane coupling agent ETP, and 0.1 parts of explosion-proof fiber;

[0068] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0069] The preparation method of the flame retardant modified bentonite and the silane coupling agent ETP is the same as that in Example 1.

[0070] Comparative Example 3

[0071] A coating material for anode copper casting, comprising the following components by weight: 70 parts of magnesium chromium oxide, 35 parts of aluminum silicon powder, 3 parts of flame retardant modified bentonite, 0.3 parts of modified CMC, 6 parts of 3-isocyanate propyl triethoxy silane, and 0.1 parts of explosion-proof fiber;

[0072] A method for preparing a coating material for anode copper casting comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, 3-isocyanate propyl triethoxy silane and explosion-proof fiber are uniformly stirred to obtain the coating material for anode copper casting.

[0073] The preparation method of the flame retardant modified bentonite and modified CMC is the same as that in Example 1.

[0074] The test method for the suspension rate is to take 100mL of evenly stirred coating material, add it into a measuring cylinder, and then let it stand for 24 hours, observe the stratification in the measuring cylinder and read the volume of the clear layer. The volume of the suspension is obtained by subtracting the volume of the clear layer from 100mL. The proportion of the volume of the suspension is the suspension rate of the coating. After reading the volume of the clear layer, the suspension rate of the coating can be calculated according to the formula: A=(100-V) / 100×100%, where: A-suspension rate; V-volume of the clear layer after the coating is allowed to stand, in mL. The test steps for the leveling of spray paint are as follows: place a T-4 viscosity cup on a bracket 100 cm away from the glass plate, then use a measuring cylinder to measure 50 mL of the coating material and pour it into the T-4 viscosity cup. The coating material flows to the glass plate through the T-4 viscosity cup and disperses around the glass plate. After a period of time, when the coating flow stabilizes, use a ruler to measure the diameter of the area covered by the coating on the glass plate to judge the leveling of the coating; the larger the diameter of the area covered on the glass plate, the better the leveling of the coating, but the leveling cannot be too large, otherwise the coating will drip. The test method for the strength of spray coating is to measure the bonding strength of the coating by dropping sand. Place the T-4 viscosity cup 100cm above the glass sheet, which is coated with coating material, and place the glass sheet on a fixed bracket at an angle of 45° to the horizontal plane; then add sand to the T-4 viscosity cup. During the operation, sand needs to be added to the T-4 viscosity cup continuously, and the T-4 viscosity cup continues to drop sand on the surface of the glass sheet coated with coating material until the glass sheet is washed out with a circular hole of about 2-4mm and the glass sheet is exposed; then collect the fallen sand and weigh the total mass of the sand, which is used as the strength of the spray coating. The oxygen index value is determined according to the ASTMD2863 standard on the FTAⅡ oxygen index instrument of the British PL company. The mixed gas is O2 / N2, the gas flow rate is 4.2cm / s, and the sample is fixed vertically in the combustion tube, so that the oxygen and nitrogen mixed gas flows from bottom to top. Use an igniter to ignite the top of the sample, while recording and observing the burning length of the sample, and compare it with the specified criteria. Test a group of samples in different oxygen concentrations to determine the minimum oxygen concentration for the plastic to maintain balanced combustion. Express it as a percentage of the oxygen content in the mixture, oxygen concentration % = oxygen flow rate / (oxygen flow rate + nitrogen flow rate) × 100%. The compressive strength test requires the use of a mechanical or hydraulic tensile testing machine. The testing machine should apply stress uniformly at a specified rate, and its range should ensure that the maximum stress applied to the sample is greater than 10% of the range. First, place the sample in the center of the pressure plate of the testing machine, and then apply pressure to the sample. Record the maximum load of the sample before it reaches failure, that is, the compressive strength value. Test conditions: 110℃×24h.

[0075] The coatings and coatings obtained in the examples and comparative examples were tested, and the results are shown in Tables 1 and 2.

[0076] Table 1 Appearance properties

[0077] sample Test results Example 1 Good spreadability, high bonding strength, no cracking during baking, and no obvious scouring after application. Example 2 Good spreadability, no cracking during baking, high sample strength after baking, and no obvious scouring after application. Example 3 Good spreadability, no cracking during baking, high sample strength after baking, and no obvious scouring after application. Example 4 Good spreadability, no cracking during baking, high sample strength after baking, and no obvious scouring after application. Comparative Example 1 The paint clumps and settles, and the material lumps powderize after baking. Comparative Example 2 The paint clumps and settles, and the material lumps powderize after baking. Comparative Example 3 The paint is too thin and dripping occurs, the casting surface is rough, the bonding strength is low, and the spreadability is poor.

[0078] Table 2 Physical properties

[0079] sample Suspension rate (%) Leveling (cm) Bond strength (g) Oxygen index value (%) Compressive strength (MPa) Example 1 99.2 14.0 139 34 16.8 Example 2 99.3 15.5 150 36 17.6 Example 3 98.6 14.9 148 33 16 Example 4 98.9 14.4 141 34 16.3 Comparative Example 1 98.0 12.4 125 18 13 Comparative Example 2 98.1 12.5 125 34 13.5 Comparative Example 3 96.5 13.2 130 33 12.6

[0080] It can be seen from the results in Table 1 and Table 2 that the coatings prepared in Examples 1-4 have good coating properties, high suspension rate, leveling property, bonding strength, oxygen index value and compressive strength, and their performance can meet the application requirements; compared with Comparative Examples 1-3, flame retardant modified bentonite, modified CMC and silane coupling agent ETP are added in the embodiments of the present invention, wherein the preparation method of the flame retardant modified bentonite is: firstly modifying o-cresol epoxy resin with triphenyl phosphate to prepare flame retardant epoxy resin, then modifying silica sol with flame retardant epoxy resin to prepare organic modified silica sol, and finally modifying bentonite with organic modified silica sol to obtain flame retardant modified bentonite; the flame retardant modified bentonite particles have a negative charge, and the same sex The particles repel each other, and it is difficult for them to aggregate into large particles, so the suspension performance is greatly improved, and the organic modified silica sol also has excellent bonding effect, so the flame retardant modified bentonite can improve the suspension and bonding strength of the coating at the same time, and the flame retardant performance of the coating is greatly improved, and the flame retardant modified bentonite modified by organic polymer and the modified CMC work synergistically, which can significantly improve the dispersion of the coating and greatly enhance the bonding strength between the coating and the copper mold anode plate; by compounding flame retardant modified bentonite, modified carboxymethyl cellulose and silane coupling agent ETP, the bonding strength between the components of the coating and the copper mold anode plate is significantly enhanced, and the protective function of the coating can be fully exerted.

[0081] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0082] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A coating material for anode copper casting, characterized in that: The invention comprises the following components in parts by weight: 60-70 parts of magnesium chromium oxide, 25-35 parts of aluminum silicon powder, 1-3 parts of flame retardant modified bentonite, 0.1-0.3 parts of modified carboxymethyl cellulose, 3-6 parts of silane coupling agent ETP, and 0.05-0.1 parts of explosion-proof fiber; The preparation method of the flame retardant modified bentonite is: Step S1, adding o-cresol epoxy resin, triphenyl phosphate and dicyandiamide to a mixed solution of N-methylformamide and acetone in sequence, stirring and mixing evenly, heating and refluxing at 150-170° C. for 3-6 hours, and removing the solvent to obtain a flame retardant epoxy resin; Step S2, in a protective atmosphere and under stirring conditions, ethyl acetate and acetone are uniformly mixed to obtain a mixed solvent, the flame-retardant epoxy resin obtained in step S1 is dissolved in the mixed solvent, and silica sol is added, and the mixture is reacted at a constant temperature of 55-75° C. for 1-4 hours, the solvent is removed, and the mixture is dried to obtain modified silica particles, and the modified silica particles are redispersed in deionized water to obtain an organic modified silica sol; Step S3, at room temperature, adding the organic modified silica sol obtained in step S2 and the pretreated sodium bentonite to deionized water, stirring evenly, aging for 6-12 hours, filtering, drying, and crushing to obtain flame retardant modified bentonite; The preparation method of the modified carboxymethyl cellulose is as follows: at room temperature and under stirring conditions, the carboxymethyl cellulose is completely dissolved in deionized water, octylphenol polyoxyethylene ether and dibutyltin dilaurate are added respectively, mixed evenly, and then diphenylmethane diisocyanate is added to carry out a cross-linking reaction, the cross-linking temperature is 25-35° C., the cross-linking time is 30-60 min, and vacuum drying is performed to obtain the modified carboxymethyl cellulose; The preparation method of the silane coupling agent ETP is as follows: under normal temperature and pressure conditions, 3-isocyanate propyl triethoxysilane and m-aminophenylacetylene are added to tetrahydrofuran, the mixture is stirred for reaction for 1-3 hours, the tetrahydrofuran is evaporated to obtain a light yellow viscous liquid, and the liquid is allowed to stand at room temperature until yellow-white spherulites are precipitated, which is the silane coupling agent ETP.

2. The coating material for anode copper casting according to claim 1, characterized in that: The particle size distribution of the magnesium chromium oxide is as follows: <1 mm accounts for 45%, 1-3 mm accounts for 25%, and 3-5 mm accounts for 30%.

3. The coating material for anode copper casting according to claim 1, characterized in that: The particle size distribution of the aluminum silicon powder is: <1mm accounts for 15%, 1-3mm accounts for 25%, 3-6mm accounts for 35%, and >6mm accounts for 25%.

4. The coating material for anode copper casting according to claim 1, characterized in that: The mass ratio of o-cresol-formaldehyde epoxy resin, triphenyl phosphate, dicyandiamide, N-methylformamide and acetone in step S1 is 20:6-10:0.5-1.5:4-6:4-6.

5. The coating material for anode copper casting according to claim 1, characterized in that: In step S2, the mass ratio of the flame retardant epoxy resin to the silica sol is 0.5-1.5:20, and the amount of the flame retardant epoxy resin added to the mixed solvent is 0.05-0.2 g / mL; the mass percentage of silicon dioxide in the silica sol is 30-40%, and the particle size is 50-100 nm.

6. The coating material for anode copper casting according to claim 1, characterized in that: The mass ratio of the organic modified silica sol and the pretreated sodium bentonite in step S3 is 0.5-2:

8. The pretreatment process of the sodium bentonite is as follows: after calcination at 400-500° C., crushing and sieving to obtain pretreated bentonite with a particle size of 150-200 mesh.

7. The coating material for anode copper casting according to claim 1, characterized in that: In the preparation process of the modified carboxymethyl cellulose, the mass ratio of carboxymethyl cellulose, octylphenol polyoxyethylene ether, dibutyltin dilaurate and diphenylmethane diisocyanate is 60:1-2:2-4:20-30; the mass percentage of carboxymethyl cellulose in the deionized water is 2-4%.

8. The coating material for anode copper casting according to claim 1, characterized in that: During the preparation of the silane coupling agent ETP, the amount of 3-isocyanate propyltriethoxysilane added to tetrahydrofuran is 0.15-0.2 g / mL, and the amount of aminophenylacetylene added to tetrahydrofuran is 0.06-0.1 g / mL.

9. The method for preparing a coating material for anode copper casting according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: according to the component proportion, magnesium chromium oxide, aluminum silicon powder, flame retardant modified bentonite, modified carboxymethyl cellulose, silane coupling agent ETP and explosion-proof fiber are uniformly stirred to obtain a coating material for anode copper casting.

Citation Information

Patent Citations

  • A copper anode casting mold repair material and its application

    CN107244900B

  • A method for resource utilization of waste magnesia-chrome bricks from copper smelting

    CN115403395B

  • Copper anode casting die repairing material and application thereof

    CN107244900A

  • Silane modified bi-component flame-retardant adhesive and preparation method thereof

    CN116925686A